Soccer intensity according to playing position in a Chilean professional youth league team - Yáñez Sepúlveda, Rodrigo.; Cubillos, Patricio; Cortés Roco, Guillermo.; Reyes Amigo, Tomás.; Hurtado Almonacid, Juan.; Navarro, Felipe; Titus, Astrid; Olivares Arancibia, Jorge Eduardo. (Federación Española de Docentes de Educación Física, 2024)
Background. Soccer is a collective sport that generates high bioenergetic demands, but at present there is little evidence on the analysis of game intensity in youth soccer players in Chile. Objective. To compare the external load according to playing position in young soccer players (U-19) of a professional soccer league team. Methods. Sixteen young Chilean soccer players belonging to a professional team aged between 17 and 19 years (18.2 ± 0.32), who were distributed according to playing position as defenders (n=6), midfielders (n=5) and forwards (n=5), participated in the study. The intensity of play during five games of the final phase of the Chilean first division championship was evaluated with a Catapult® wireless global positioning system (GPS) using a sampling frequency of 10Hz. Results. Differences were found in total distance in the first half between defenders and forwards, between defenders and midfielders with a medium effect size (η²p=0.302), there were also differences in sprinting > 25-30 km/h between defenders and forwards, between defenders and midfielders, and between forwards and midfielders with a small effect size (η²p =0, 225), finally there were differences in high intensity meters between forwards and midfielders, between forwards and defenders with a medium effect size (η²p =0.252), while very high intensity sprinting (> 31km/h) presented differences only between forwards and midfielders with a small effect size (η²p =0. 137). Conclusions. In the present study, differences were found in external loading according to playing position, with forwards presenting higher intensities of play during the match compared to defenders and midfielders. These results provide reference data that can be used for decision making by technical teams for tactical optimization, individualization of training and recovery management in young players.
Intensidad del fútbol según posición de juego en un equipo de la liga profesional juvenil de Chile
Keywords: GPS; RHIE; Fútbol; Deportes; Rendimiento atlético